Penggunaan Model Discovery Learning Berorientasi HOTS Pada Materi Vektor di SMA Negeri 1 Muncang - Yana, Desna Widdanie (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2023)
Developments in information, automation, computing, and communication greatly affect the education sector. This requires adjusting the concept and application of learning in the classroom, including the integration of learning with higher order thinking skills. The purpose of this study is to describe learning practices in applying higher-order thinking skill-oriented learning. The type of research used in this research is qualitative with descriptive method. This research was conducted in two stages, namely preparation and implementation. The activities carried out in the preparatory stage are mapping of basic competencies, formulating competency achievement indicators, selecting learning models, and developing learning tools. The activities carried out at the implementation stage are carrying out learning activities oriented to higher order thinking skills using the discovery learning model. By systematically and carefully preparing lesson plans (RPP), the lessons implemented are not only HOTS oriented, but also integrate strengthening character education, literacy and 21st century skills.